Analisa Pengaruh Variasi Tekanan dan Jarak Semprot Nozzle Terhadap Daya Output Pada Instalasi Turbin Pelton - Yusuf, Muhammad Ridwan; Hasbi, Muhammad; Samhuddin, Samhuddin (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2019)
This study aims to examine Pelton Turbines for Micro Hydro Power Plant Systems (PLTMH) with pressure variations and spray nozzle distances to output power in pelton turbine installations, in pressure variations namely pressure 0.5, 1, 1.5, 2 and 2.5 bar and variations the spray nozzle distance is 6, 9 and 12 cm. The tested turbine has a single nozzle, with a nozzle diameter of d = 10 mm, the number of blades Z = 14 pieces and a diameter of a turbine of 14 cm. The research began with the design, manufacturer of Pelton turbine installations and electrical installations. The parameters measured in the test are flowrate, pressure on the nozzle, turbine rotation, electric voltage and current, temperature and diameter of the working fluid. The results obtained the highest output power at a spray distance of 6 cm Nozzle and 2.5 bar pressure of 110.14 Watts with 88.11% Turbine Efficiency while the lowest Output power was obtained at a spray distance of 12 cm and a pressure of 0.5 bar of 17.07 Watts with a Turbine Efficiency of 51.2%.Keywords: Pelton Turbine, Output Power, Turbine Efficiency, Pressure Variation and Nozzle Spraydistance.